2009
DOI: 10.1007/s12185-009-0435-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of recombinant factor VIII safety: KOGENATE® and Kogenate® FS/Bayer

Abstract: The use of factor VIII (FVIII) concentrates in the treatment of hemophilia A has raised important safety issues, historically of pathogen transmission and increasingly of inhibitor development to FVIII treatment. While manufacturing processes of current recombinant FVIII products have been shaped entirely around preventing pathogen transmission, the same modifications that afford a greater margin of safety could affect immunogenicity of the product, consequences of which could only be seen through long-term cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Changes in BHK manufacturing practices between Product B and Product D might have led to increased immunogenicity, 36 but the number of patients treated with Product B in both the RODIN study and in our cohort was too small for comparison with Product D. rFVIII molecules produced by BHK and CHO cells differ in several respects, such as the degree of tyrosine residue sulphation and type of glycosylation. 37 The presence of specific glycan chains might affect dendritic cell uptake and thereby modify rFVIII immunogenicity.…”
Section: Possible Biological Explanations and Implicationsmentioning
confidence: 84%
“…Changes in BHK manufacturing practices between Product B and Product D might have led to increased immunogenicity, 36 but the number of patients treated with Product B in both the RODIN study and in our cohort was too small for comparison with Product D. rFVIII molecules produced by BHK and CHO cells differ in several respects, such as the degree of tyrosine residue sulphation and type of glycosylation. 37 The presence of specific glycan chains might affect dendritic cell uptake and thereby modify rFVIII immunogenicity.…”
Section: Possible Biological Explanations and Implicationsmentioning
confidence: 84%
“…Sixteen of these 32 patients had high-titer antibodies and 16 had low (<5 BU/mL) and/or transient titers [9]. Sixteen of these 32 patients had high-titer antibodies and 16 had low (<5 BU/mL) and/or transient titers [9].…”
Section: Clinical Trials In Previously Untreated Patientsmentioning
confidence: 99%
“…A metaanalysis of the clinical trials demonstrated that cumulatively, the incidence of de-novo inhibitor development was 8.2% in PUPs with <20 EDs, 1.5% in those with 20-100 EDs and 0.2% in PTPs with >100 EDs [9].…”
mentioning
confidence: 99%
“…In the 1980s, the increased demand for clotting factor concentrates, combined with concerns over the safety of pdCFCs, led to the development of recombinant clotting factor concentrates (recombinant CFCs) . The manufacturing and purification processes involved are designed to reduce the risk of viral contamination .…”
Section: Recombinant Clotting Factor Concentratesmentioning
confidence: 99%